Design, synthesis, biological evaluation, and bio-computational modeling of imidazo, thieno, pyrimidopyrimidine, pyrimidodiazepene, and motifs as antimicrobial agents - El-Ahwany Maged F.; Assy Mohamed G.; Sherif Mohamed H.; Soliman Mohamed R.; Titi Abderrahim; Touzani Rachid; El-Gendey Marwa S.; Shehab Wesam S.; Abdellattif Magda H. (Heterocyclic Communications, 2023)
In the drug chemistry industry, synthesizing a talented exclusive series of aza-polyheterocyclic compounds was crucial. Aminopyrimidine nucleus reacted with two equivalents of benzaldehyde in the presence of KOH as a starting material to bring about imidazopyrimidine derivative, which experienced intermolecular cyclization using carbon disulfide, Br2/AcOH, and/or HNO2 to produce thiazole, thieno, and/or nitro pyrimidine derivative, respectively. Accordingly, the nucleus of Aminopyrimidine was prepared and used to develop the novel polyheterocyclic systems acylated with two moles of succinic anhydride to furnish the imidazolopyrimidine derivative. Benzylidene ethyl cyanoacetate and aminopyrimidine undergo (3 + 4) intermolecular cycloaddition 1,3 H shift followed by hydrolysis and after CO2 evolution provided diazepine derivative. The diazepine derivative was attained due to the cyclo-condensation of the starting material and acetylacetone. Moreover, the structure of the novel synthesized compound series was exploited and verified via spectroscopic approaches. The synthesized series were tested for antimicrobial activity against gram-positive and gram-negative bacterial strains and antifungal activity. The thienopyrimidine derivatives and diazepine exhibited unusual antimicrobial activity. Furthermore, the molecular docking studies confirmed the biological studies with Molecular Operating Environment and petro orisis molinspiration studies, which proved the activity of compounds 4, 5, 7, 10, 13, and 16.